2015
DOI: 10.1097/md.0000000000001803
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Primary Malignancy Risk in Patients With Cervical Cancer in Taiwan

Abstract: To evaluate the risk of secondary primary malignancy (SPM) in patients with cervical cancer using a nationwide population-based dataset.Patients newly diagnosed with cervical cancer between 1997 and 2011 were identified using Taiwan's National Health Insurance database. Patients with antecedent malignancies were excluded. Standardized incidence ratios (SIRs) for SPM were calculated by comparing with the cancer incidence in the general population. Risk factors for cancer development were analyzed using Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Although breast‐conserving surgery plus radiotherapy played an important part in the management of BC, complications remain a troubling by‐product. Some studies demonstrated an association between radiotherapy and the elevated risk of subsequently SPM among patients with prostate and cervical cancers . A secondary malignancy induced by initial treatment represents one of the most serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast‐conserving surgery plus radiotherapy played an important part in the management of BC, complications remain a troubling by‐product. Some studies demonstrated an association between radiotherapy and the elevated risk of subsequently SPM among patients with prostate and cervical cancers . A secondary malignancy induced by initial treatment represents one of the most serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous or metachronous presence of primary gastric cancer and primary gynaecological tumor (ovary, uterus, and breast) has been described in 15 (0.6%) cases out of 2,668 patients with gastric cancer (34). Of note, it has been also found that patients with a personal history of uterine cancer are at 1.38-fold (95% CI: 1.09-1.72) increased risk of developing primary gastric cancer (35). Finally, women with hereditary inactivating mutations in the E-cadherin gene CDH1 are at increased risk for both gastric cancer and breast carcinoma (6).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Teng et al reported that a significantly higher risk was observed for secondary cancers of the uterus (Teng et al, 2015). In a report from Japan, a site-based analysis revealed an excess of second cancers in the rectum and uterine body and occurrences of acute leukemia (Ota et al, 2007).…”
Section: Introductionmentioning
confidence: 99%